2020
DOI: 10.1016/j.ssc.2020.113965
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of the α- to β-phase transition in BaD2 under high pressure

Abstract: We report high-pressure neutron diffraction, and Raman spectroscopy data from the -(Pnma) to -(P6 3 /mmc) phase transition in BaD 2 . The transition was observed at 2.53(5) GPa on pressure increase, and 1.65(5) GPa on pressure decrease, with a relatively narrow 0.20(5) GPa region of phase coexistence. We report the isothermal equations of state for the -phase at 300 K and the -phase at both 300 K and 480 K, and have calculated the entropy change through the transition. The Raman data show that a low energy Ba-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Note that the 4f split site has approximately half the ADP as the 2d. Verbraeken et al and Ridley et al both found that the D1 site showed a relatively large ADP in the HT phase. , Due to the covariance of U , occupancy, and coordinates, it is possible to find different ADPs. Specifically, Verbraeken et al.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Note that the 4f split site has approximately half the ADP as the 2d. Verbraeken et al and Ridley et al both found that the D1 site showed a relatively large ADP in the HT phase. , Due to the covariance of U , occupancy, and coordinates, it is possible to find different ADPs. Specifically, Verbraeken et al.…”
Section: Resultsmentioning
confidence: 98%
“…24 In the high pressure Ni 2 In form, the cations have been suggested to occupy the special 2c, 2a, and 2d sites by analogy with BaF 2 . 21 Previous studies at high temperature 1 or high pressure 24 on BaD 2 have shown that the D1 atom can be placed on either the 2d or 4f split site. 1,24 We also refined the NPD data using both the 2d and 4f models and found that both returned satisfactory fits.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the evolution of the atomic positions under high pressure, where the largest changes observed corresponded to the D(2) sites followed by the Ba/ Ca sites. 27,28 The high compressibility of the a-axis was attributed to the movement of the D(2) sites, while Raman spectroscopy showed that there was mode softening that was a result of instability in the Ba sites. Similar to the high pressure studies, these high temperature results show that modifications to the D(2) sites, and to a lesser degree the Ba sites, are main contributing factors that lead to the phase transition in BaD 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%